Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1063/1.4903167
|View full text |Cite
|
Sign up to set email alerts
|

On square-wave-driven stochastic resonance for energy harvesting in a bistable system

Abstract: Energy harvesting in a quad-stable harvester subjected to random excitation AIP Advances 6, 025022 (2016)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The research led by K. Nakano and M. P. Cartmell (Su et al, 2013;Zhang et al, 2014;Zheng et al, 2014) was the first group to definitively experimentally demonstrate stochastic resonance for VEH while showcasing its amplification effect from ambient broadband noise. Their work has shown the modulation of the bistable potential well (Hu et al, 2012;Su et al, 2013Su et al, , 2014 while also mapping out a comprehensive theoretical and experimental framework for stochastic resonance in a rotational VEH context (Zheng et al, 2014). The rotational scenario has been experimented in automotive wheels (Zhang et al, 2014(Zhang et al, , 2015(Zhang et al, , 2016 where the external ambient road vibration acts as the broadband noise excitation and wheel speed-dependent vibration acts as the specific periodic signal.…”
Section: Stochastic Resonance For Vehmentioning
confidence: 99%
“…The research led by K. Nakano and M. P. Cartmell (Su et al, 2013;Zhang et al, 2014;Zheng et al, 2014) was the first group to definitively experimentally demonstrate stochastic resonance for VEH while showcasing its amplification effect from ambient broadband noise. Their work has shown the modulation of the bistable potential well (Hu et al, 2012;Su et al, 2013Su et al, , 2014 while also mapping out a comprehensive theoretical and experimental framework for stochastic resonance in a rotational VEH context (Zheng et al, 2014). The rotational scenario has been experimented in automotive wheels (Zhang et al, 2014(Zhang et al, , 2015(Zhang et al, , 2016 where the external ambient road vibration acts as the broadband noise excitation and wheel speed-dependent vibration acts as the specific periodic signal.…”
Section: Stochastic Resonance For Vehmentioning
confidence: 99%
“…McInnes et al [11] first suggested the possibility of improving the performance of nonlinear bi-stable harvesters using stochastic resonance and provided a numerical analysis to support such a proposition. By adding a periodically modulated excitation to a randomly excited bi-stable harvester, it has been found that the power is improved by about eight times over the power of the same harvester without stochastic resonance [12]. Following this fundamental work, a bi-stable harvester was designed by Zheng et al [13,14] to experimentally demonstrate stochastic resonance as a strategy for stochastic energy harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, SR phenomena have been observed in Schmitt trigger circuit by Fauve [ 4 ] and a bidirectional ring laser by McNamara [ 5 ], which confirmed the SR theory. Since then, this nonlinear phenomenon has received much attention from the physics community, which was widely used in weak-signal detection and energy harvesting [ 6 , 7 , 8 , 9 ]. Recent researches show that SR not only appears in bistable systems [ 10 ], but also in monostable oscillators [ 11 ], chaotic systems [ 12 ], and time-delay systems [ 13 ].…”
Section: Introductionmentioning
confidence: 99%